Form and function remixed: developmental physiology in the evolution of vertebrate body plans. (8th May 2014) - Newman, Stuart A.
Abstract: The most widely accepted model of evolutionary change, the Modern Evolutionary Synthesis, is based on the gradualism of Darwin and Wallace. They, in turn, developed their ideas in the context of 19th century concepts of how matter, including the tissues of animals and plants, could be reshaped and repatterned. A new physics of condensed, chemically, electrically and mechanically excitable materials formulated in the 20th century was, however, readily taken up by physiologists, who applied it to the understanding of dynamical, external condition‐dependent and homeostatic properties of individual organisms. Nerve conduction, vascular and airway dynamics, and propagation of electrical excitations in heart and brain tissue all benefited from theories of biochemical oscillation, fluid dynamics, reaction–diffusion‐based pattern instability and allied dissipative processes. When, in the late 20th century, the development of body and organ form was increasingly seen to involve dynamical, frequently non‐linear processes similar to those that had become standard in physiology, a strong challenge to the evolutionary synthesis emerged. In particular, large‐scale changes in organismal form now had a scientific basis other than gradualistic natural selection based on adaptive advantage. Moreover, heritable morphological changes were seen to be capable of occurring abruptly with little or no genetic change, with involvement of the external environment, and in preferred directions. This paper discusses three examples of morphological motifs of vertebrate bodies and organs, the somites, the skeletons of the paired limbs, and musculoskeletal novelties distinctive to birds, for which evolutionary origination and transformation can be understood on the basis of the physiological and biophysical determinants of their development.